2015
DOI: 10.3174/ajnr.a4245
|View full text |Cite
|
Sign up to set email alerts
|

Fast Contrast-Enhanced 4D MRA and 4D Flow MRI Using Constrained Reconstruction (HYPRFlow): Potential Applications for Brain Arteriovenous Malformations

Abstract: BACKGROUND AND PURPOSE: HYPRFlow is a novel imaging strategy that provides fast, high-resolution contrast-enhanced time-resolved images and measurement of the velocity of the entire cerebrovascular system. Our hypothesis was that the images obtained with this strategy are of adequate diagnostic image quality to delineate the major components of AVMs. MATERIALS AND METHODS: HYPRFlow and 3D TOF scans were obtained in 21 patients with AVMs with correlative DSA examinations in 14 patients. The examinations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 36 publications
(37 reference statements)
0
29
0
Order By: Relevance
“…increased WSS in AVM feeding arteries was more prevalent with severe patient symptoms. Another study (55) demonstrated the utility of 4D flow MRI combined with contrast-enhanced 4D MRA (HYPRFlow) to obtain high-resolution angiography and quantitative flow assessment of the entire AVM vasculature. Additional studies explored the comprehensive evaluation of cerebral 3D blood flow patterns, regional flow characteristics and post-embolization induced hemodynamic changes in patients with cerebral AVMs (27, 56, 57), providing an individualized assessment of AVM hemodynamics and longitudinal evaluation of treatment-induced flow redistribution.…”
Section: Evaluation Of Cerebral Vascular Malformationsmentioning
confidence: 99%
“…increased WSS in AVM feeding arteries was more prevalent with severe patient symptoms. Another study (55) demonstrated the utility of 4D flow MRI combined with contrast-enhanced 4D MRA (HYPRFlow) to obtain high-resolution angiography and quantitative flow assessment of the entire AVM vasculature. Additional studies explored the comprehensive evaluation of cerebral 3D blood flow patterns, regional flow characteristics and post-embolization induced hemodynamic changes in patients with cerebral AVMs (27, 56, 57), providing an individualized assessment of AVM hemodynamics and longitudinal evaluation of treatment-induced flow redistribution.…”
Section: Evaluation Of Cerebral Vascular Malformationsmentioning
confidence: 99%
“…This technique has been used with success to characterize AVMs, which similarly to DAVFs requires high spatial and temporal resolution due to their rapid arteriovenous shunting and small feeding vessels. (18, 19) HYPRFlow is well suited for characterizing AVMs and DAVFs because whole brain coverage allows the whole lesion to be characterized which is possible because the relative sparsity of vessels in 3D space allows for the use of undersampling techniques such as radial acquisition (VIPR). Previous work has demonstrated that use of the HYPR reconstruction method provides improved SNR compared to radially sampling k -space with a sliding window reconstruction method (33)…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are only a few studies investigating the diagnostic value of 4D flow MRI for the assessment of AVM flow characteristics. Recent reports include the quantification of flow and WSS in patients using a highly optimised radial 4D flow technique 203,204 . Additional studies demonstrated the potential of 4D flow MRI for the evaluation of global and regional AVM flow characteristics as illustrated in Fig.…”
Section: Applicationsmentioning
confidence: 99%